Analysis Of ICT Laboratory Management Through SOP Implementation (Comparative Study at Karsa Mulya Vocational School and MAN Palangka Raya City) - Athariq Maulana; Ade S Permadi; MN Fitriyanto (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2024)
Information and Communication Technology (ICT) facilities are a crucial component in supporting learning activities in schools. The implementation of effective Standard Operating Procedures (SOPs) is the key to ensuring efficient and orderly management of ICT laboratories, as well as ensuring the sustainability of facility use (Astriyani et al., 2024). This study aims to analyze the management of Information and Communication Technology (ICT) laboratories at SMK Karsa Mulya and MAN Palangka Raya City through the implementation of Standard Operating Procedures (SOPs). This study uses a qualitative descriptive method with a comparative case study approach. Data collection was carried out through observation, interviews, and documentation. The results of the study show that both schools have implemented SOPs in managing ICT laboratories, but there are differences in the scope and level of implementation. These differences are influenced by several factors, such as management support, personnel awareness, and resource availability. This study concludes that consistent implementation of SOPs can improve the effectiveness and efficiency of ICT laboratory management. This study provides recommendations for other schools to develop and implement comprehensive SOPs in managing ICT laboratories.